Comparison of Step Outputs for Waist and Wrist Accelerometer Attachment Sites. Issue 4 (April 2015) - TUDOR-LOCKE, CATRINE; BARREIRA, TIAGO V.; SCHUNA, JOHN M.
ABSTRACT Purpose The objective of this study is to compare step outputs obtained from waist and wrist accelerometer attachment sites under laboratory and free-living conditions. Methods Under the laboratory condition, participants concurrently wore ActiGraph accelerometers at their waist and nondominant wrist while walking/running at treadmill speeds between 14 and 188 m·min−1. Visually counted steps served as a criterion standard. Participants then wore both accelerometers for 7 d. All accelerometer step data were processed applying both the manufacturer's default and low-frequency extension filters. Paired sample t-tests were used to evaluate mean differences in criterion steps per minute and the four (attachment site × filter) estimates produced from the waist- and wrist-worn accelerometers in the laboratory study. Free-living differences in mean steps per day detected between the waist and wrist (considering both filters) were computed. Results Relative to visually counted steps, the waist attachment site generally outperformed the wrist attachment site at most speeds, regardless of the applied filtering process. Under free-living conditions, the waist-worn accelerometer detected 6743 ± 2398 (default filter) and 13, 029 ± 3734 (low-frequency extension) steps per day. The concurrently worn wrist accelerometer detected 9301 ± 2887 (default filter) and 15, 493 ± 3958 (low-frequency extension) steps per day. Conclusion The wrist attachment site detected consistently fewer visually counted steps than the waist attachment site at most treadmill speeds during laboratory testing. In contrast, the wrist attachment site produced a higher average step count (ranging from approximately 2500 to 8700 more steps per day under free-living conditions, dependent on the filtering process applied) than the waist attachment site under free-living conditions. In conclusion, step outputs obtained from waist- and wrist-worn accelerometer attachment sites are generally not comparable under either laboratory or free-living conditions.